The importance of women in 21st century rural Spain: Challenges and opportunities - Bulmer, Elena; Riera-Roca, Magali; Prado- Higuera, Cristina del (International Journal of Management and Sustainability, 2025)
The recent wave of urbanization has resulted in a significant increase in the number of people living in urban areas, surpassing those in rural areas. This concentration of people in cities promotes resource efficiency and economic growth. In Spain, 85% of the population live in urban (and peri-urban) areas, compared to 15% in rural areas. In recent times, the expression “España Vaciada” or “Empty Spain” has become popular to describe the depopulation problem in rural parts of the country. The objective of this qualitative study was to measure and analyze the opinions and perceptions that rural women have regarding the problems they are currently experiencing as well as their role as change agents in potentially promoting rural socio-economic resurgence both in the short and long term. We implemented a ten-question online survey using Google Forms from March 28th to May 13th, 2024. 216 women residing in towns and/or rural areas from 39 of the 50 provinces in Spain answered the survey. Most female interviewees affirmed that they played a very or fairly important role in rural areas, and most considered that their role would become more relevant in coming years. The depopulation problem was primarily caused by three main issues: a lack of employment, depopulation, and inadequate transportation. Although the role of women is a pillar for their communities, their numbers in rural Spain have been dwindling, and the territories have become, through time, more masculinized, thereby creating the imperative of creating socioeconomic opportunities for rural women to redress the resultant gender imbalance.